KEPUASAN PELAYANAN SURAT TANDA MELAPOR (STM) WARGA NEGARA ASING DI KEPOLISIAN SEKTOR PONTIANAK UTARA - Maâ€™mur E.21109008, Agus (FISIP Universitas Tanjungpura, 2014)
The writing of this thesis is to provide an understanding of â€œthe letter of the sign to report for foreign citizens in the Northern Pontianak sector policingâ€,problems concerning the mechanisms of the ministry letter report for foreign citizens that occurred in Northern Pontianak sectorÂ policing is attractive enough for researched,because of the existing problems of the Ministry report this letter must have had 4 things : simplicity, efficiency, fairness and clarity,so can thus be known clearly support that can provide satisfaction to the rapporteur in providing service to report the license plate for the foreign citizens. it can be concluded about the service Melpor Certificate in Police Sector North Pontianak can conclude a few things about the North Pontianak Police Sector Performance based approach proses.Tingkat Police Sector North Pontianak performance in carrying out the functions to be performed in the standard medium in which efficiency, ease, clarity and justice in a service is still in a low level results also expected to be useful as a reference for the government, especially in identifying the organizational culture to improve the quality of care at the reporting reporting Reporting Certificate of Foreign Nationals. Furthermore, the contribution of scientific thought BASED variables based on the data analysis results showed that individual initiative in, integration, control, tolerance for conflict, communication patterns, tolerance for risk measures, guidance, support of identity management and reward systems to service quality, show that implies that the effect of the data based on the analysis of the results showed that it contains to be criticized in order to improve service quality Certificate Reporting Foreign Nationals in the Police Sector North PontianakÂ Keyword : letter report, foreign citizens, ease, efficient, justice, clarity